MATERIAL AND STERILIZATION CENTER: PERCEPTION OF THE NURSING TEAM ABOUT THEIR WORK AND IMPORTANCE FOR PATIENT SAFETY - Gratão, Márcia Simon Sgambatti; Higa, Elza de Fátima Ribeiro; Medeiros, Rodolfo de Oliveira [UNESP]; de Moraes, Magali Aparecida Alves; de Lima, Aparecida Bezerra; Gimenez, Fabiana Veronez Martelato (Ludomedia Unipessoal Lda, 2023)
Introduction: The Material and Sterilization Center (CME) is the sector responsible for processing materials for use in health care. The CME has the assistance of the Hospital Infection Control Commission (CCIH) team, with the objective of preparing and guaranteeing the quality of all stages of processing, in order to reduce the rates of infection related to health care and, thus, contribute to patient safety. Objectives: To analyze the literary evidence and the understanding that the CME nursing team has regarding the processing of health materials, current legislation, about the importance of their work for patient safety. Method: Qualitative field research, based on Hermeneutics-Dialectics, developed in a public hospital in the interior of the State of São Paulo. 21 professionals from the team participated through semi-structured interviews. Results: From the analysis of the meanings obtained in the speeches of the participants, six analytical categories emerged: 1. Understanding the stages of the work process in the CSSD; 2. Misunderstanding of ANVISA legislation (RDC 2605, 156, 15); 3. Understanding the importance of the CME's work for patient safety; Final considerations: From the Hermeneutics-Dialectics, it was evident how nursing understands its work process and the importance for patient safety, indicating the needs and demands for carrying out its activities and the need to continue learning in everyday life from work.
CENTRO DE MATERIAL E ESTERILIZAÇÃO: PERCEPÇÃO DA EQUIPE DE ENFERMAGEM SOBRE SEU TRABALHO E IMPORTÂNCIA PARA A SEGURANÇA DO PACIENTE
Keywords: Attitudes and practices in health; Knowledge; Nursing team; Patient safety; Sterilization